2016
DOI: 10.1177/1744806916636385
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between astrocytic CXCL12 and microglial CXCR4 contributes to the development of neuropathic pain

Abstract: Background Chemokine axis chemokine C-X-C motif ligand 12/C-X-C chemokine receptor type 4 (CXCL12/CXCR4) is an emerging pain modulator, but mechanisms for its involvement in neuropathic pain remain unclear. Here, we aimed to study whether CXCL12/CXCR4 axis modulated the development of neuropathic pain via glial mechanisms. In this study, two mouse models of neuropathic pain, namely partial sciatic nerve ligation (pSNL) model and chronic post-ischemia pain (CPIP) model, were used.Results In the dorsal horn of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 52 publications
4
69
0
1
Order By: Relevance
“…Herein, we found that blocking CXCR4 by antagonist AMD3100 could raise EAAT 2 and EAAT 1 mRNA expression, and decrease the Connexin 43 and Connexin 30‐Hemichannel Activity in spinal cord astrocytes. Furthermore, the CXCL12 peptide activated the CXCR4 localized in the neurons and astrocytes leading to pain‐related hypersensitivity in naive rats, which is in line with previous studies . Thirdly, decreasing CXCR4 by inhibiting astrocyte metabolism may partially prevent CXCL12‐induced neuropathic pain.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Herein, we found that blocking CXCR4 by antagonist AMD3100 could raise EAAT 2 and EAAT 1 mRNA expression, and decrease the Connexin 43 and Connexin 30‐Hemichannel Activity in spinal cord astrocytes. Furthermore, the CXCL12 peptide activated the CXCR4 localized in the neurons and astrocytes leading to pain‐related hypersensitivity in naive rats, which is in line with previous studies . Thirdly, decreasing CXCR4 by inhibiting astrocyte metabolism may partially prevent CXCL12‐induced neuropathic pain.…”
Section: Discussionsupporting
confidence: 88%
“…CXCL12/CXCR4 axis also plays an important role in the neuropathic pain caused by peripheral nerve injury. In the pSNL model, CXCL12/CXCR4 signaling increased the production of pro‐inflammatory cytokines in the microglia, which triggered the development of neuropathic pain . In the SNI model, CXCL12 showed a long‐lasting upregulation in neurons and microglia, while CXCR4 was mainly increased in the neurons and astrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, dorsal horn neurons exhibit elevated expression of the chemokine SDF-1α/CXCL12 in a CIPN model [76][77][78], CXCL13 in a rat SNL model [79], and CCL3 and its receptor CCR5 in CCI in rats [80•, 81, 82]. Proinflammatory cytokines such as interferon-γ activate spinal microglia, a process that underlies many of the neuropathy-induced changes in spinal neuron behavior, Lidocaine injection close to the injury of post-surgical neuroma patients [50] Dose-dependent reduction in spontaneous and evoked pain scores by more than 80% Persistent post-herniorrhaphy pain Bupivacaine infiltration of tender points, ultrasound-guided, placebo-controlled Significantly greater analgesia and reduced evoked pain response when compared with placebo Persistent pain after breast cancer surgery (PPBCS) (pilot study)…”
Section: Changes In the Spinal Cordmentioning
confidence: 99%
“…The pathophysiological mechanisms are multifactorial and have not been completely elucidated. Pain is processed by neural networks, and increasing lines of evidence suggest that IR-induced secondary inflammatory pain occurs concomitantly with glial activation both at remote sites and in an injured spinal cord through various forms of communication between neurons-glia or glia-glial cells [3,4]. Microglia and astrocytes, which are the main glial cells in the spinal cord, constitute the blood-spinal cord barrier (BSCB) and act as the first responders to pathological stimuli [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…The sequential activation of and crosstalk between microglia and astrocytes is now known to be performed by soluble mediators, such as adenosine, growth factors, inflammatory chemokines and cytokines [3,8,9]. Among these mediators, chemokines are 8-14-kDa secreted proteins with conserved cysteine residues in their sequences.…”
Section: Introductionmentioning
confidence: 99%